1996
DOI: 10.1063/1.871569
|View full text |Cite
|
Sign up to set email alerts
|

Regimes of the magnetized Rayleigh–Taylor instability

Abstract: Hybrid simulations with kinetic ions and massless fluid electrons are used to investigate the linear and nonlinear behavior of the magnetized Rayleigh-Taylor instability in slab geometry with the plasma subject to a constant gravity. Three regimes are found, which are determined by the magnitude of the complex frequency ϭ r ϩi␥. For ͉͉Ӷ⍀ i (⍀ i ϭ ion gyrofrequency͒, one finds the typical behavior of the usual fluid regime, namely the development of ''mushroom-head'' spikes and bubbles in the density and a stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 52 publications
(89 reference statements)
3
28
0
Order By: Relevance
“…The growth rate in the Hall þ Gyro run appears to be the combination of the Hall and the Gyro runs. This tendency is similar to that reported by Winske,7 in which the wave number space is divided into three regions depending upon the dominance of the FLR effect at a high wave number region. It is noteworthy that the unstable mode is completely stabilized at k > 25 in the Hall þ Gyro run, making a clear difference from that in the previous work in which the stabilization is incomplete.…”
Section: Initial Equilibrium and Linear Growth Ratesupporting
confidence: 76%
“…The growth rate in the Hall þ Gyro run appears to be the combination of the Hall and the Gyro runs. This tendency is similar to that reported by Winske,7 in which the wave number space is divided into three regions depending upon the dominance of the FLR effect at a high wave number region. It is noteworthy that the unstable mode is completely stabilized at k > 25 in the Hall þ Gyro run, making a clear difference from that in the previous work in which the stabilization is incomplete.…”
Section: Initial Equilibrium and Linear Growth Ratesupporting
confidence: 76%
“…The finite Larmor radius (FLR) effect on interchange instability was investigated first by Roberts and Taylor (1962), who demonstrated that this effect can stabilize the instability in a short-wavelength limit kL n 1, where k is the wave number and L n is the density gradient scale length. Huba (1996) and Winske (1996) confirmed the stabilization effect. Huba (1996) also suggested that, since the FLR leads to the drift velocity of developing perturbations proportional to the diamagnetic drift velocity, this may lead to phase mixing the unstable perturbations within a growth period, which may stabilize the instability.…”
Section: Account For the Magnetic Fieldsupporting
confidence: 58%
“…The important condition for initiating the R-T instability is, as mentioned above, the existence of a force normal to the interface between the two fluids. It may be the gravitational force, the inertial force resulting from deceleration of plasma moving toward or out from the reconnection layer, the force due to the curvature of magnetic field lines, and others (see also Winske, 1996). The R-T instability may develop both at the magnetopause, following compression by the solar wind dynamic pressure (Gratton et al, 1996), and in the magnetotail (Pritchett and Coroniti, 2010;Guzdar et al, 2010;Lapenta and Bettarini, 2011).…”
Section: Rayleigh-taylor (Interchange) Instabilitymentioning
confidence: 99%
“…(9), comes out of Eqs. (1)- (7). The UNS equation could also model the nonlinear modulation of the high-frequency mode in the electron beam plasma.…”
Section: Discussionmentioning
confidence: 99%